Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1088/1361-648x/ac75a1
|View full text |Cite
|
Sign up to set email alerts
|

Surface nanopatterning by ion beam irradiation: compositional effects

Abstract: Surface nanopatterning induced by ion beam irradiation (IBI) has emerged as an effective nanostructuring technique since it induces patterns on large areas of a wide variety of materials, in short time, and at low cost. Nowadays, two main subfields can be distinguished within IBI nanopatterning depending on the irrelevant or relevant role played by the surface composition. In this review, we give an up-dated account of the progress reached when surface composition plays a relevant role, with a main focus on IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 236 publications
0
4
0
Order By: Relevance
“…A separate study done by the same group also showed that excellent ripple ordering can be achieved by Xe + ions at low ion incidence angles even at moderate ion fluences and also for a diverging incident ion beam [26,27]. However, these results may be affected by inadvertent, uncontrolled co-deposition of metallic impurities during the irradiation process [8,28]. Further, ripple ordering properties at particular incidence energies have been observed to depend on the bombarding ion species [29], while non-standard irradiation setups like sequential and/or dual IBI [21,30,31] have been also employed with the goal to reduce pattern defects.…”
Section: Introductionmentioning
confidence: 95%
“…A separate study done by the same group also showed that excellent ripple ordering can be achieved by Xe + ions at low ion incidence angles even at moderate ion fluences and also for a diverging incident ion beam [26,27]. However, these results may be affected by inadvertent, uncontrolled co-deposition of metallic impurities during the irradiation process [8,28]. Further, ripple ordering properties at particular incidence energies have been observed to depend on the bombarding ion species [29], while non-standard irradiation setups like sequential and/or dual IBI [21,30,31] have been also employed with the goal to reduce pattern defects.…”
Section: Introductionmentioning
confidence: 95%
“…Ion beam induced patterning and structuring in materials is a rapidly evolving field with a wide range of applications, including micro-and nanofabrication, surface modification, and materials engineering. Reports are available in the existing literature describing the use of this versatile technique for creation of diverse morphologies over different classes of materials [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Vazquez et al [12] have given an up-dated account of the progress reached when surface composition plays a relevant role, with a main focus on ion beam irradiation surface patterning with simultaneous co-deposition of foreign atoms. Further, they have reviewed the advances in ion beam irradiation of compound surfaces as well as ion beam irradiation systems where the ion employed is not a noble gas species.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that isolated dots can be fabricated by ion irradiation on prepatterned nano-templates [3][4][5][6] ,which is applicable for advanced electronic, optoelectronic and magnetic device development. A good number of experimental and theoretical studies on ion-induced surface pattern formation are reported [7,8], however, the understanding is not yet complete. The most important unexplored part is the chemical effect on such structure formation and the structure transformation at very high ion fluence.…”
Section: Introductionmentioning
confidence: 99%